A case of placenta increta in placenta previa: a rare case report - Das, Badal; Roy, Debobroto; Sarkar, Malay; Das, Krishna Pada; Khatun, Nazmin; Moulick, Aritrick (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Placenta increta, one type of morbidly adherent placenta, is characterized by entire or partial absence of the decidua basalis, and by the incomplete development of the fibrinoid or Nitabuch’s layer and villi actually invading the myometrium. When the internal os is covered partially or completely by placenta, it is described as a placenta previa. Simultaneously these two complications occurring in a post LSCS scarred uterus is a very rare scenario and anticipated frequently to cause catastrophic obstetric outcome. A 32-years-old woman of second gravida, para 1, with previous history of LSCS 7 years back, with living issue one, admitted in our hospital at 35 weeks 5 days gestation with asymptomatic placenta previa with placenta increta. The case was diagnosed effectively by ultrasonography. Intra-operatively, compression sutures and bilateral uterine artery ligature was tried to control hemorrhage which were failed and a quick decision of caesarean hysterectomy was done. Preserving both ovaries, total hysterectomy was the only option to save the mother in our case. Other options attempting to preserve uterus could have ended up with grave consequences in this case. This was a very rare case of asymptomatic placenta previa with placenta increta in a post LSCS scarred uterus and it was successfully managed by judicious caesarean hysterectomy.